Statistical Evaluation Of The Larvicidal Effect Of Diflubenzuron On Culex Pipiens Larval Stages - Djordjević Milutin (Sciendo, 2015)
Diflubezuron is increasingly used in areas where mosquito larvae developed resistance to other insecticides. In our community diflubenzuron is not used to control mosquito larvae. Two formulations of 1% diflubenzuron (on corn-cob EF-1, and zeolite EF-2) were tested on Culex pipiens L (larvae) on one canal in the Belgrade suburb area. The effect was followed for seven weeks after application of the formulations. Formulation EF1 achieved a reduction in mosquito L1L2 larvae between 23.9% and 89.4%. The change was statistically significant the 21st and 28th day (p<0.001), 35th and 42nd day (p<0.01) and 49th day (p<0.05). The maximal reduction obtained by formulation EF2 was 69.1%. The accomplished reduction was significant on the 28th and 42nd day (p<0.001), 35th day (p<0.01) and 21st (p<0.05). Both formulations have maintained a good residual effect on the lower developmental larval stages. Maximum reduction achieved by EF1 on L3L4 larvae was 97.4%. Reduction of larvae was high between the 7th and 42nd day (66.4 - 97%). Statistically significant values were recorded on the 21st, 28th and 35th day. Formulation EF2 achieved a reduction of 99.5%. A statistically significant reduction in the value of mosquito larvae was obtained on the 14th, 21st, 28th, 35th and 42nd day.